Factors Affecting the Adhesion of Flour Particles to Stainless-steel Surfaces and Vacuum Dry-cleaning - Ian M. Klug; Bradley P. Marks; Teresa M. Bergholz; Sanghyup Jeong (Journal of Food Protection)
Recent outbreaks and recalls linked to flour-based products have highlighted the need for improved cleaning methods in low-moisture environments. The factors affecting adhesion forces of flour particles, and the vacuum cleaning methodologies to overcome these forces, need to be better understood. The objectives of this study were to: (1) Measure electrostatic charge build-up in flour under different environmental conditions (20, 40, 60% relative humidity at room temperature), (2) quantify how powder size (US standard No. 60–80 or 80–100 mesh), electrostatic charge (charged and uncharged), and relative humidity impact the force required to remove the powder from an electropolished 304 stainless steel coupon (8 × 8 × 0.2 cm), and (3) determine the most effective vacuum nozzle angle (0, 45, 90° relative to the surface) for cleaning. Chargeability (nC) of flour samples was assessed using Faraday cup electrometry, while the surface adhesion force of the flour particles was measured using a custom-built impact tester. The surface cleanliness after vacuum treatments was assessed using ATP (adenosine triphosphate) swabs and a luminometer. Charged flour samples at 20% relative humidity (RH) exhibited a significantly higher charge compared to those at 40 and 60% RH. Within the 60–80 mesh range, charged flour showed higher adhesion rates than uncharged samples at both 20 and 40% RH. However, in the 80–100 mesh range, charged flour did not show a significant difference in adhesion when compared to uncharged samples at any RH level. Additionally, at 60% RH, surface residues measured by ATP were significantly lower for a vacuum angle of 90° than for 0° across both 60–80 mesh and 80–100 mesh size ranges of wheat flour. The vacuum cleaning treatment proved capable of overcoming the increase in adhesion from triboelectric forces; however, trace flour residues were still detected on stainless steel surfaces postvacuuming, indicating that vacuuming alone may be insufficient.